(untitled) (INTERNATIONAL SEMINAR, 2024)
This study explores the implementation of Project-Based Learning (PBL) as an instructional strategy to enhance students’ essay writing skills. The research was conducted in a secondary education context, where students often struggle with structuring ideas and maintaining coherence in essay writing. Through the PBL approach, students engaged in collaborative projects requiring them to draft, revise, and present essays based on real-world topics. Data collection involved pre- and post-tests, classroom observations, and student reflections to evaluate the effectiveness of the intervention. The findings revealed that PBL significantly improved students’ ability to organize ideas, develop arguments, and express thoughts with clarity. Additionally, the collaborative aspect of PBL fostered a supportive learning environment that encouraged peer feedback and critical thinking. This study concludes that PBL is an effective pedagogical approach to promote writing proficiency and recommends its broader adoption in educational settings.